Evaluation and management of toxicity of cytoreductive surgery/hyperthermic intraperitoneal chemotherapy: the initial experience of a single centre study - Lemstrova, Radmila; Flasarova, Dominika; Spisarova, Martina; Melichar, Bohuslav; Lovecek, Martin; Havlik, Roman; Neoral, Cestmir; Mohelnikova-Duchonova, Beatrice; Klos, Dusan (Biomedical papers, 2020)
Background: Cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) is a treatment modality for peritoneal surface malignancies with efficacy reported in many trials. Discrepancies, however, in the indication criteria, the extent of the surgical procedure, HIPEC regimens and toxicity evaluation represent a problem when comparing this method with other therapeutic modalities. Methods: We describe the initial experience with CRS/HIPEC using different chemotherapy regimens (oxaliplatin, cisplatin, mitomycin C and doxorubicin) at the Comprehensive Oncology Centre Olomouc. Results: A perioperative mortality of 2% and perioperative morbidity of 11%, according to Clavien-Dindo were observed. Interestingly, all these patients underwent HIPEC with oxaliplatin 460 mg/m2. The median duration of admission to hospital was 6 days in the intensive care unit (range 2-28 days) and 7 days in the surgical ward (range 1-21 days). Hospital admission did not exceed 2 weeks in 75% of patients. These results are consistent with the published results of large centres performing this treatment modality mainly due to pre-operative preparation of patients and pre-treatment and post-treatment management of HIPEC/CRS toxicity. Evaluation of the efficacy in terms of time to progression and overall survival (OS) is limited by the short follow up period. Conclusion: CRS/HIPEC performed is a safe method with low perioperative mortality.
Keywords: cytoreductive surgery; hyperthermic intraperitoneal chemotherapy; oxaliplatin; mitomycin C; cisplatin; toxicity; adverse events; morbidity